2001
DOI: 10.1007/bf02762109
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional neglect and physical abuse in children of alcoholics

Abstract: Alcoholism in parents of malnourished and injured children are frequently ignored in routine clinical evaluation. If the risk children are identified early some of the morbidity can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…It has a disproportionately high association with deliberate self-harm [41], high-risk sexual behaviour, HIV infection [42], tuberculosis [43], oesophageal cancer [44], liver disease and duodenal ulcer [45,46]. Alcohol misuse wreaks a high social cost [47,48]. A study from the state of Karnataka in South India estimated that monetizable direct and indirect costs attributable to people with alcohol dependence alone was more than three times the profits from alcohol taxation and several times more than the annual health budget of that state [49].…”
Section: Alcohol-related Problemsmentioning
confidence: 99%
“…It has a disproportionately high association with deliberate self-harm [41], high-risk sexual behaviour, HIV infection [42], tuberculosis [43], oesophageal cancer [44], liver disease and duodenal ulcer [45,46]. Alcohol misuse wreaks a high social cost [47,48]. A study from the state of Karnataka in South India estimated that monetizable direct and indirect costs attributable to people with alcohol dependence alone was more than three times the profits from alcohol taxation and several times more than the annual health budget of that state [49].…”
Section: Alcohol-related Problemsmentioning
confidence: 99%
“…There have been attempts to study various aspects of children of people with alcohol dependence from India and some published literature is available that looks at various domains in the same sample. [1–4]…”
Section: Introductionmentioning
confidence: 99%
“…Rao[1] found that alcoholism was present in parents of malnourished (49.4%) and injured children (45%).…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, víctimas durante el período gestacional presentan mayor oportunidad de hijos con bajo peso al nacer, parto pretérmino, muerte en el periodo neonatal y un patrón de lactancia menos adecuado (23) . Todos estos factores, que pueden ser productos de la violencia, se han visto relacionados con malnutrición en niños (14,(24)(25)(26)(27) . Por otro lado, el estrés al que están sometidos los niños que viven en estos hogares puede llevar a estados de alta actividad inflamatoria y prooxidante, como fue observado en 2010 por Houphouet (28) , donde la malnutrición estuvo asociada con estado inflamatorio, indicado por aumento de proteína C reactiva, la cual, además, se acompañaba de depleción proteica, especialmente de albúmina, lo que podría ser un factor contribuyente a la desnutrición (29,30) .…”
Section: Discussionunclassified